ISLAM, SANTET, AND COLLECTIVE VIOLENCE: TRANSITIONAL POLITICS AND MEMORY IN BANYUWANGI, 1998–1999 - Kusairi, Latif; Dhanang Respati Puguh; Yety Rochwulaningsih (UIN Raden Mas Said Surakarta, 2025)
This article investigates how the discourse of witchcraft (santet) was mobilized into collective violence in Banyuwangi in 1998–1999, and how Islam, local tradition, and the political stigma of anti-communism intersected in the escalation of killings. The article combines event reconstruction and discourse reading with theoretical lenses drawn from Charles Tilly’s framework on collective violence, Johan Galtung’s concept of structural violence, and Claude Lévi-Strauss’s insights on myth and collective imagination. It’s connect structural conditions, actor mobilization, and the production of cultural meaning. This article argue that the violence—claiming more than 194 lives—cannot be reduced to a spontaneous religious clash or a purely cultural aberration. Instead, it was a product of transitional politics, in which economic crisis, uncertain authority, and the lingering anti-communist stigma enabled santet to operate as a moral classificatory instrument facilitating labelling, dehumanization, and the legitimation of killing. In the aftermath, the tragedy reshaped Banyuwangi’s social narratives through transformations in collective memory, identity reconstruction, and the articulation of new religious and cultural narratives during the Reformasi period. This article contributes to the understanding of santet by integrating structural, mobilizational, and cultural-imaginary dimensions to explain it not merely as a “local belief,” but as a politically consequential mechanism in the production of collective violence in Banyuwangi.